Meteorological data from ice-free areas in Yukidori Zawa, Langhovde, Kizahashi Hama, Skarvsnes and Skallen in Sôya Coast, East Antarctica during 2014–2015 - KUDOH, Sakae; TAKAHASHI, Kunio T.; ISHIHARA, Tomoko; TSUJIMOTO, Megumu; NAKAI, Ryosuke; SUZUKI, Atsushi C.; TANABE, Yukiko; UCHIDA, Masaki; IMURA, Satoshi (2015)
Fig. 1 | http://polaris.nipr.ac.jp/~parc/pub/v004/nipr_parc_363_0019.doc departmental bulletin paper